Penguatan Seni Budaya Kontemporer Dadak Reog Pereng Melalui Pemaknaan, Energi, dan Spiritualisme - Agus Purwantoro; Viola Dinda Dwi Hapsari; Rahmanu Widayat; Deny Tri Ardianto; Arsya Aurasalwa (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The traditional Reog Ponorogo art from East Java has long been adopted and preserved in Pereng Village, Mojogedang, Karanganyar, home to several active Reog communities. The “KW” (imitation) Dadak Reog performance, now integral to the village’s cultural identity, requires transformation to align with local culture and strengthen its contemporary identity. This study explores the meaning, energy, and spiritualism of Reog Pereng and community-based revitalization strategies using an ecoart approach. Employing a participatory qualitative ethnographic method, data were collected through interviews, observations, and field documentation. Findings reveal that Reog Pereng holds deep spiritual dimensions through rituals, offerings, and symbolic performances, while fostering social solidarity and cross-generational regeneration. Key challenges include limited funding and organizational structures, yet opportunities for revitalization emerge through artistic innovation, contemporary collaborations, and branding Pereng as a Creative Village.